PREFERENCE OF TEMORA STYLIFERA (CALANOID COPEPOD) FOR PLANKTONIC CILIATES AND EGG PRODUCTION - Wiadnyana, Ngurah N. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1995)
The investigation of feeding and egg production of the calanoid co pepod Temora stylifera was carried out between September and November 1988. The copepods were fed on natural ciliates and phytoplankton assemblage. Planktonic ciliates composed of 2.20 to 3.83 g C l -1 representing 15.2 to 58.7% of total biomass in standing stock. They were consumed by these copepods at rates ranging from 11.25 to 38.14 g C mg DW-1Â d-1 or about 27.6 to 74.8% of total food consumed. The increase of ciliates/phytoplankton biomass ratio in the food consumed by the copepods in the all experiments indicates the preference for ciliates, in which as a good quality of food they can improve the rates of copepods egg production.